Identical Fe-N4 Sites with Different Reactivity: Elucidating the Effect of Support Curvature - Jakub, Zdeněk; Planer, Jakub; Hrůza, Dominik; Shahsavar, Azin; Pavelec, Jiří; Čechal, Jan (ACS applied materials & interfaces, 2025)
Detailed atomic-scale understanding is a crucial prerequisite for rational design of next-generation single-atom catalysts (SACs). However, the sub-ångström precision needed for systematic studies is challenging to achieve on common SACs. Here, we present a two-dimensional (2D) metal-organic system featuring Fe-N4 single-atom sites, where the metal-organic structure is modulated by 0.4 Å corrugation of an inert graphene/Ir(111) support. Using scanning tunneling microscopy and density functional theory, we show that the support corrugation significantly affects the reactivity of the system, as the sites above the support "valleys" bind TCNQ (tetracyanoquinodimethane) significantly stronger than the sites above the "hills". The experimental temperature stability of TCNQ varies by more than 60 °C, while computations indicate more than 0.3 eV variation of TCNQ adsorption energy across the Fe-N4 sites placed atop different regions of the corrugated graphene unit cell. The origin of this effect is steric hindrance, which plays a role whenever large molecules interact with neighboring single-atom catalyst sites or when multiple reactants coadsorb on such sites. Our work demonstrates that such effects can be quantitatively studied using model SAC systems supported on chemically inert and physically corrugated supports.
Keywords: single atom catalysis; adsorption; Fe−N4 site; 2D metal−organic frameworks; density functional theory; scanning tunneling microscopy